Role for a Cindr-Arf6 axis in patterning emerging epithelia. - Johnson, R.I.; Sedgwick, A.; D'Souza-Schorey, C.; Cagan, R.L. (Molecular Biology of the Cell, 2011)
Patterning of the Drosophila pupal eye is characterized by precise cell movements. In this paper, we demonstrate that these movements require an Arf regulatory cycle that connects surface receptors to actin-based movement. dArf6 activity-regulated by the Arf GTPase-activating proteins (ArfGAPs) dAsap and dArfGAP3 and the Arf GTP exchange factors Schizo and dPsd-promoted large cellular extensions; time-lapse microscopy indicated that these extensions presage cell rearrangements into correct epithelial niches. During this process, the Drosophila eye also requires interactions between surface Neph1/nephrin adhesion receptors Roughest and Hibris, which bind the adaptor protein Cindr (CD2AP). We provide evidence that Cindr forms a physical complex with dArfGAP3 and dAsap. Our data suggest this interaction sequesters ArfGAP function to liberate active dArf6 elsewhere in the cell. We propose that a Neph1/nephrin-Cindr/ArfGAP complex accumulates to limit local Arf6 activity and stabilize adherens junctions. Our model therefore links surface adhesion via an Arf6 regulatory cascade to dynamic modeling of the cytoskeleton, accounting for precise cell movements that organize the functional retinal field. Further, we demonstrate a similar relationship between the mammalian Cindr orthologue CD2AP and Arf6 activity in cell motility assays. We propose that this Cindr/CD2AP-mediated regulation of Arf6 is a widely used mechanism in emerging epithelia.